An investigation into effect of nitriding on fatigue life of piston - Hilmee, Mat Jusoh (2008)
The piston is the crucial part of the internal combustion engine. Prediction of fatigue life on piston for four stroke engine using variable amplitude loading is presented. The objectives of this project are to predict fatigue life of piston for four stroke engine using stress-life method, to identify the critical locations, to investigate the effect of mean stress and to optimize the component material. The structural and finite element modelling has been performed using a computer aided design and finite element analysis software package. The finite element model of component then analyzed using the S-N approach. Finally, the stress-strain state of component obtained previously will be use as input for the fatigue life. The effected mean stress and materials optimize was also investigated. The failure of piston can result in devastating damage to the engine including all the components from a tiny screw till a huge belting system. Life of piston needs to be improved to prevent from any unpleasant problems. The result of the analysis show that there are no serious failure occurs at the part of the piston. However it is observed that the minimum predicted life at the critical location is 102.38e-7 under variable amplitude loading for stress life approach. The optimization result show that AISI 4042 is the most superior material among the others.